Pengaruh Citra Merek dan Preceived Quality Terhadap Keputusan Pembelian Shampoo Merek Lifebuoy - Basuki Rahmat (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the effect of brand image and preceived quality on purchasing decisions of Lifebuoy Shampoo users in South Tangerang. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, brand image has a significant effect on purchasing decisions by 41.8%, hypothesis testing obtained t count> t table or (8.215> 1.661). Preceived quality has a significant effect on purchasing decisions by 37.4%, hypothesis testing obtained t count> t table or (7.488> 1.661). Brand image and preceived quality simultaneously have a significant effect on purchasing decisions with the regression equation Y = 10.724 + 0.400X1 + 0.341X2 and the influence contribution is 50.1%, the hypothesis test obtained F count> F table or (46.652> 2,700).